PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI SEBELUM DAN SEMASA PANDEMI COVID - Iin Zubaedah; Sparta Sparta (Ibs Press, 2023)
This study aims to obtain empirical evidence from Managerial Ownership, Institutional Ownership, Independent Board of Commissioners, and the Audit Committee which is an indicator of Good Corporate Governance as an independent variable, and other variables namely Leverage and Firm Size as control variables, and Pandemic Covid as a dummy variable, on the dependent variable namely Earnings Management in Manufacturing Companies sub-sector Food and Beverage listed on the Indonesia Stock Exchange (IDX). Discretionary accruals with the Kothari model used as a proxy for earnings management. The sample was obtained by purposive sampling method with predetermined criteria, and resulted 40 in manufacturing companies sub-sector food and beverage in the 2016-2020 period with a total of 200 data. Descriptive statistics and multiple regression were used as data analysis methods. The results of this study can be summarized as follows. The first regression analysis, namely before the covid pandemic period, showed that Institutional Ownership and Audit Committee had a significant negative effect on Earnings Management, while Managerial Ownership, Independent Board of Commissioners, Leverage, and Firm Size had no effect on Earnings Management. The second regression analysis, before and during the covid pandemic, showed that Managerial Ownership, Institutional Ownership, and Leverage had a significant negative effect on Earnings Management. Meanwhile, the Independent Board of Commissioners, Audit Committee, Firm Size, and the Covid Pandemic have no effect on Earnings Management. Based on this explanation, it can be concluded that the implementation of Good Corporate Governance in Manufacturing companies in the Food and Beverage Subsector can be said to be still relatively ineffective, because only Managerial Ownership, Institutional Ownership and Audit Committees in this study are able to carry out their duties effectively to minimize the practice of earnings management happened to the company.